DNA‐Metalization: Synthesis and Properties of Novel Silver‐Containing DNA Molecules (Adv. Mater. 24/2016). Issue 24 (16th June 2016) - Eidelshtein, Gennady; Fardian‐Melamed, Natalie; Gutkin, Vitaly; Basmanov, Dmitry; Klinov, Dmitry; Rotem, Dvir; Levi‐Kalisman, Yael; Porath, Danny; Kotlyar, Alexander
Abstract : D. Porath, A. Kotlyar, and co‐workers transform DNA to a conducting material by metalization through coating or chemical modifications, as described on page 4839. Specific and reversible metalization of poly(dG)‐poly(dC) DNA by migration of atoms from silver nanoparticles to the DNA is demonstrated. As the transformation occurs gradually, novel, truly hybrid molecular structures are obtained, paving the way to their usage as nanowires in programmable molecular electronic devices and circuits.